Prenatal Alcohol Exposure, Attention‐Deficit/Hyperactivity Disorder, and Sluggish Cognitive Tempo. (20th July 2012) - Graham, Diana M.; Crocker, Nicole; Deweese, Benjamin N.; Roesch, Scott C.; Coles, Claire D.; Kable, Julie A.; May, Philip A.; Kalberg, Wendy O.; Sowell, Elizabeth R.; Jones, Kenneth L.; Riley, Edward P.; Mattson, Sarah N.; et al.
Abstract : Background: Children with heavy prenatal alcohol exposure often meet criteria for attention‐deficit/hyperactivity disorder (ADHD). ADHD research has examined subtype differences in symptomatology, including sluggish cognitive tempo (SCT). This construct is defined by behavioral symptoms including hypoactivity and daydreaming and has been linked to increased internalizing behaviors. The current study examined whether similar findings are displayed in children with prenatal alcohol exposure. Methods: As part of a multisite study, caregivers of 272 children (8 to 16 years) completed the SCT Scale and Child Behavior Checklist (CBCL). Four groups were included: alcohol‐exposed children with ADHD (ALC+; n = 75), alcohol‐exposed children without ADHD (ALC−; n = 35), nonexposed children with ADHD (ADHD; n = 60), and nonexposed children without ADHD (CON; n = 102). SCT and CBCL scores were analyzed using 2 (exposure) × 2 (ADHD) analyses of variance. Pearson's correlations measured the relationships between SCT, CBCL, and Full Scale IQ (FSIQ). Discriminant function analysis examined whether SCT items could accurately classify groups. Results: Analyses revealed significant main effects of exposure and ADHD on SCT and internalizing and externalizing scores and significant interaction effects on SCT and internalizing scores. SCT significantly correlated with internalizing, externalizing, and attention ratings in all groups and with FSIQ in ALC+. Discriminant function analysis indicated that specific SCT items could distinguish ALC− from CON. Conclusions: Alcohol‐exposed children exhibited elevated SCT scores. Elevations were related to increased parent ratings of internalizing and externalizing behaviors and attention. These findings are observed in alcohol‐exposed children regardless of ADHD symptoms and specific SCT items proved useful in distinguishing exposed children, suggesting clinical utility for this measure in further defining the neurobehavioral profile related to prenatal alcohol exposure.